1988
DOI: 10.1152/ajpgi.1988.255.3.g352
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory opioid receptors in canine pylorus

Abstract: In 18 anesthetized dogs, antroduodenal and pyloric motility was monitored in vivo by a sleeve and perfused side-hole manometric assembly and by antral and duodenal serosal strain gauges. Close intra-arterial injection to the pylorus of dynorphin-(1-13) (Dyn) for kappa-receptors, [D-Pen2,5]enkephalin (DPen2,5-Enk) for delta-receptors, and [N-Me-Phe3-D-Pro4]morphiceptin (PL017) and [D-Ala2,N-Me-Phe4,Gly5-ol]enkephalin (DAGO) for mu-receptors showed no excitatory effect in the pylorus. When pyloric motor activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

1990
1990
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 0 publications
1
24
0
1
Order By: Relevance
“…This region has been shown to contain a very high density of opioid-containing neurones in several species (Edin et al, 1980;Ferri et al, 1987;Allescher et al, 1988). We found that exogenous opioids reduced the amplitude of excitatory and inhibitory junction potentials.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…This region has been shown to contain a very high density of opioid-containing neurones in several species (Edin et al, 1980;Ferri et al, 1987;Allescher et al, 1988). We found that exogenous opioids reduced the amplitude of excitatory and inhibitory junction potentials.…”
Section: Discussionsupporting
confidence: 55%
“…Emptying of solid meals was significantly slowed by the enkephalin analogue DAMME (D-Ala2, MePhe4, Met(O-Ol-enkephalin; FK33-824) (Sullivan et al, 1981), but others reported that naloxone did not affect gastric emptying (Feldman et al, 1980). Allescher et al (1988) found that exogenous opioid agonists inhibited motor activity of the canine pylorus in vivo. Naloxone antagonized these effects, demonstrating the presence of functional opioid receptors in the canine pylorus.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…MORs are widely distributed on cell membranes in the body and are present in the central nervous system (45)(46)(47) including at the spinal level (48), on peripheral nerves (49), and in the gastrointestinal tract (41,(50)(51)(52).…”
Section: Opioid Drugsmentioning
confidence: 99%
“…Opioids affect a variety of functions including motility (41,51,52,(61)(62)(63)(64)(65) and secretion (57), and both μ-and κ-receptors are involved (40).…”
Section: Remifentanilmentioning
confidence: 99%